Obesity interferes with the orosensory detection of long-chain fatty acids in humans–. Issue 5 (12th February 2014) - Chevrot, Michael; Passilly-Degrace, Patricia; Ancel, Déborah; Bernard, Arnaud; Enderli, Géraldine; Gomes, Marlène; Robin, Isabelle; Issanchou, Sylvie; Vergès, Bruno; Nicklaus, Sophie; Besnard, Philippe
ABSTRACT: Background: The association between the orosensory detection of lipids, preference for fatty foods, and body mass index (BMI; in kg/m 2 ) is controversial in humans. Objective: We explored the oral lipid-sensing system and the orosensory-induced autonomic reflex system in lean and obese subjects. Design: Lean (BMI: 19 to <25; n = 30) and obese (BMI >30; n = 29) age-matched men were enrolled. Their oral threshold sensitivity to linoleic acid (LA) was determined by using a 3-alternative forced-choice ascending procedure, and their eating habits were established by the analysis of 4 consecutive 24-h food-consumption diaries. The effect of brief oral lipid stimulations on plasma triglyceride [(TG)pl] concentrations was analyzed in overnight-fasted lean and obese individuals subjected to a whole-mouth stimulation (sip-and-spit procedure) with a control or 1% LA emulsions for 5 min according to a within-subject randomized design. Results: A large distribution of LA detection was shown in both groups. Mean detection thresholds were 0.053% (wt:wt) and 0.071% (wt:wt) in lean and obese subjects, respectively. No relation between the LA detection threshold and BMI was observed. The 5 subjects who detected only the higher concentration of LA (5% wt:wt) or were unable to distinguish properly between control and LA emulsions were obese. An analysis of dietary habits showed that these obese LA nontasters consumed more lipids and energy than did all other subjects. Brief whole-mouth stimulations (sip-and-spit procedure) with a control or 1% LA emulsion revealed an LA-mediated rise in (TG)pl concentrations in overnight-fasted, lean subjects. The origin of this change seemed to be hepatic. This (TG)pl upregulation was not shown in obese subjects, which suggested that obesity led to disturbances in the oral-brainstem-periphery loop. Conclusion: Altogether, these data strongly suggest that obesity may interfere with the orosensory system responsible for the detection of free long-chain fatty acids in humans. This trial was registered at clinicaltrials.gov as NCT02028975.